Spatio-Cultural Wisdom In Disaster Mitigation: Dual-Hazard Adaptation In The Minangkabau Highlands Of Indonesia - Erna Juita; Dasrizal Dasrizal; Mohd Hairy Ibrahim; Arie Zella Putra Ulni; nefilinda nefilinda (LPPM Universitas PGRI Sumatera Barat, 2025)
Indonesia’s disaster mitigation policies have historically relied on technocratic paradigms that often marginalize indigenous knowledge. The research specifically aims to document, analyze, and critically interpret the operationalization of indigenous knowledge across the phases of disaster management: pre-disaster, during-disaster, and post-disaster. Guided by the social-ecological systems theory and cultural resilience framework, a qualitative descriptive approach was employed. Data were collected through field observations, in-depth interviews with community leaders and traditional authorities, and textual analysis of oral and written adat sources. A spatial vulnerability assessment was conducted to contextualize practices within the region’s geomorphological risks. The findings reveal a sophisticated, multi-layered system of risk mitigation embedded in local architecture (e.g., elevated rumah gadang), hydrological infrastructure (tabek, parit nagari), ecological zoning (rimbo larangan), and socio-religious governance (Tigo Tungku Sajarangan). These practices demonstrate high spatial adaptability and cultural coherence but show signs of erosion due to modernization, land-use change, and weakening intergenerational transmission. This study concludes that effective disaster mitigation in high-risk landscapes must transcend engineering-based approaches by integrating indigenous knowledge, normative values, and spatial-cultural contexts into formal disaster risk reduction frameworks. The novelty of this research lies in its holistic documentation of dual-hazard mitigation practices and its proposal of a spatio-cultural corrective to Indonesia’s predominantly technocratic disaster governance.